Personal and Pedagogical Interaction Factors as Determinants of Academic Achievement - Cardoso, Ana Paula (2016)
This study intends to relate self-esteem, teacher-student interaction, student-student interaction and learning performance, and its direct and indirect relationships with academic achievement. Using a sample of about 2000 Portuguese high school students, a structural model reveals that low social self-esteem directly and negatively influences teacher-student interaction and studentstudent interaction and also learning performance. Teacher-student interaction directly and positively influences student-student interaction. Teacher student-interaction and student-student interaction directly and positively influence learning performance, which in turn influences directly and positively academic achievement. Corroborating previous studies, these findings suggest that an appropriate pedagogical interaction provides an effective learning environment that enhances student´s learning outcomes, namely academic achievement. Recommendations for teachers and school managers are addressed.